Semiotic Analysis In The Anime A Silent Voice As A Representation Of Bullying On The Bstation Application - Naura Sajidah; Sri Wulandari; Dian Andriany (ann4publisher@gmail.com, 2026)
Aims. This study aims to analyze semiotics in the anime A Silent Voice as a representation of bullying on the Bstation app from Kyoto Animation studio. Methods. Directed by Naoko Yamada, this study uses Charles Sanders Peirce's semiotics theory, which consists of three elements of meaning or the Triangle of Meaning, namely Sign, Object, and Interpreter, using several data or scenes in the anime “A Silent Voice” as units of analysis, as well as using information sources in the form of documentation from the anime “A Silent Voice”. Result. The results of the study show that the anime “A Silent Voice” has a meaning of bullying categorized into three types, from Signs such as hearing aids, the “X” symbol, body gestures, representations of teacher authority, and the arrangement of space and atmosphere that function as signs that mediate the characters' experiences. The Object includes sensory disabilities, social rejection, group interaction mechanisms, school institutional structures, and mental pressure. The Interpreter includes the construction of differences, internalization of guilt, experiences of isolation, and psychological trauma. Conclusion. This anime can bring positive values to the audience watching the film by showing how bullying can be seen from the dimensions of Signs, Objects, and Interpreters by identifying and observing each scene shown in the film on the two characters, Shoko Nishimiya and Shoya Ishida.